Practical guide and spectral atlas for interpretive near-infrared spectroscopy - Workman, Jerry; Weyer, Lois. (Boca Raton, FL. : CRC Press, 2012)
'Interpretive spectroscopy provides a basis for the establishment of cause-and-effect relationships between spectrometer response and the chemical properties of the samples. Without established cause-effect relationships, the measured data will have no true predictive significance. This interpretive process is key for achieving an analytical understanding of the measurement. The popular first edition of this text delivered a unique focus on structure correlation and interpretation of spectra for the practitioner. The thoroughly updated and revised second edition expands on this by offering a full library of four color spectra in a larger format to ensure clarity and reader comprehension'--
'Preface In this second edition of The Practical Guide and Spectral Atlas for Interpretive Near- Infrared Spectroscopy, we have endeavored to expand and update the chapters, and to produce the figures in a more dramatic spectral atlas format, that is, in a four-color, 81/2 x 11 book. The color and larger graphical presentation provides richer, more detailed spectra than the first edition. This revised atlas also includes new research, editorials, supplements, and molecular structural formulas (Appendix H), including updated references and information on near-infrared (NIR) spectra. Qualitative and quantitative NIR spectroscopic methods require the application of multivariate calibration algorithms commonly referred to as chemometric methods to model spectral response to chemical or physical properties of a calibration, teaching, or learning sample set. The identification of unique wavelength regions where changes in the response of the NIR spectrometer are proportional to changes in the concentration of chemical components, or in the physical characteristics of samples under analysis, is required for a scientific understanding of cause (i.e., molecular or physical properties) and effect (i.e., spectroscopic changes), even for routine method development. The first step to developing an analytical method using NIR is to measure a spectrum of the sample using an NIR spectrophotometer. It is helpful to note that the NIR spectrum obtained by using a spectrophotometer is the result of the convolution of the measuring instrument function with the unique optical and chemical characteristics of the sample measured. The sample participates as an optical element in the spectrometer'--
Includes bibliographical references and indexes.
Keywords: Near infrared spectroscopy